ESTUDO DOS ANGULOS CLIVUS SPHENOIDALE E SPHENOIDALE EM FETOS HUMANOS (FLEXAO PRE NATAL DA BASE DO CRANIO) - Watanabe, I. S.; Madeira, M. C. (My University, 1973)
The clivus sphenoid angle and the sphenoid angle represent the basicranial flexion in the sagittal direction. Changes of this flexion may occur due to the following factors: expansion of the sphenoid sinus, height of the sphenoid body and the posterior part of the nasal cavity, brain growth, differential growth in the skull base, body posture, and individual variations. To analyze the possible variations of size of the clivus sphenoid and sphenoid angles under the influence of these factors, one hundred human fetuses (57 male and 43 female) of ages between 4 and 9 mth were utilized. The formalin preserved heads were sectioned through the median plane and the angular measurements were made by placing a sheet of transparent paper on the right hemi head and tracing the cardinal points required for each angle. The angles were then measured directly on the paper with a protractor. Some of these angles were checked from lateral roentgenographs. There are no significant differences between both sphenoid and clivus sphenoid angles. The angles of cranial base flexion remain unchanged from the 4th through the 9th fetal mth. No sexual difference could statistically be determined. The angles exhibit wide ranges of variation in all fetal ages. The factors which could determine changes in the degree of cranial flexion have no influence during the fetal period.
Study of the clivus sphenoidale and sphenoidale angles in human fetuses (prenatal basicranial flexion)